2018
DOI: 10.2175/106143017x15131012152942
|View full text |Cite
|
Sign up to set email alerts
|

Ammoniacal Nitrogen Stripping From Landfill Leachate at Open Horizontal Flow Reactors

Abstract: The ammonia nitrogen stripping process at open horizontal flow reactors was evaluated and is described in this paper. The ammonia came from landfill leachate. Superficial loads of 650 kgN-.ha-1.day-1 (phase 1), 750 kgN-.ha-1.day-1 (phase 2), and 850 kgN- Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…S4). It was worth noting that the pH of effluent in the anodic chamber remained unchanged (7 ± 0.4), which indicated that the effect of ammonia volatilization could be neglected 30 . Therefore, the mass balance and mechanisms in NH 4 + recovery will be researched in‐depth to illustrate the pathway to improve the performance of MDC.…”
Section: Resultsmentioning
confidence: 99%
“…S4). It was worth noting that the pH of effluent in the anodic chamber remained unchanged (7 ± 0.4), which indicated that the effect of ammonia volatilization could be neglected 30 . Therefore, the mass balance and mechanisms in NH 4 + recovery will be researched in‐depth to illustrate the pathway to improve the performance of MDC.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the efficiency of ammonia removal was directly connected with the applied surface laod and that the amount of organic matter in the effluent. The main advantage of this process is the ineffectiveness of organic matter degradation and the release of NH3 into the atmosphere, even though NH 3 can be an environmental hazard [40]. The methods of air stripping, followed by a series of CF and adsorption, were used to treat landfill leachate.…”
Section: Air Strippingmentioning
confidence: 99%
“…Leite et al [28] investigated and characterised the NH 3 -N stripping method at open horizontal flow reactors. The study involved the superficial load in three different phases phase 1 (650 kg N-NH 4 + ha −1 .day −1 ), phase 2 (750 kg N-NH 4 + ha −1 .day −1 ), and phase 3 (850 kg N-NH 4 + ha −1 .day −1 ).…”
Section: Ammoniacal Nitrogen (Nh 3 -N) Reduction By Air Strippingmentioning
confidence: 99%